THE IMPACT OF ALTRUISM ON REPURCHASE INTENTION IN CONSUMERS WHO USE THE BODY SHOP'S BODY MIST PRODUCTS IN SUBANG CITY - Gugyh Susandy; Rini Nuraeni (STIESA Press, 2025)
This research aims to analyze the impact of altruism on repurchase intention in consumers who use Body Mist products from The Body Shop. Altruism is measured based on consumers' attitudes towards social and environmental issues, such as The Body Shop's use of environmentally friendly ingredients. This research used a descriptive survey method with a total of 81 respondents who had used Body Mist products. Data were analyzed using simple linear regression to see the relationship between altruism and repurchase intention. The research results show that altruism has a positive and significant influence on consumers' repurchase intentions. Consumers who care about the environment tend to be more loyal and willing to make repeat purchases. These findings indicate that altruistic values can be an important factor in creating consumer loyalty towards environmentally friendly products.